rozwiąż nierówności:
8m-4(1+m)=m-3x+8<-5+14x
3x-8(1-x)≥5x-4
8m-4(1+m)=m
8m - 4 -4m =m
4m-m=4
3m=4 /:3
m = 4/3
-3x+8<-5+14x
-3x-14x < -5-8
-17x<-13 /:(-17)
x> 13/17
3x-8+8x≥5x-4
11x-5x≥-4+8
6x≥4 /:6
x≥2/3
1.
8m-4-4m=m
4m-4=m
-4=-3m /:(-3)
2.
13<17x /:17
x>13/17
3.
11x-4≥5x
-4≥-6x /:(-6)
x≥4/6
8m - 4 - 4m = m
4m - 4 =m
- 4= - 3m
4= 3m
1 1/3= m
8 < -5 + 17x
13 < 17x
13/17 < x3x-8(1-x)≥5x-4
3x - 8 + 8x ≥ 5x - 4
6x - 8 ≥ - 4
6x ≥ 4
x ≥ 2/3
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
8m-4(1+m)=m
8m - 4 -4m =m
4m-m=4
3m=4 /:3
m = 4/3
-3x+8<-5+14x
-3x-14x < -5-8
-17x<-13 /:(-17)
x> 13/17
3x-8(1-x)≥5x-4
3x-8+8x≥5x-4
11x-5x≥-4+8
6x≥4 /:6
x≥2/3
1.
8m-4(1+m)=m
8m-4-4m=m
4m-4=m
-4=-3m /:(-3)
2.
-3x+8<-5+14x
13<17x /:17
x>13/17
3.
3x-8(1-x)≥5x-4
3x-8+8x≥5x-4
11x-4≥5x
-4≥-6x /:(-6)
x≥4/6
x≥2/3
8m-4(1+m)=m
8m - 4 - 4m = m
4m - 4 =m
- 4= - 3m
4= 3m
1 1/3= m
-3x+8<-5+14x
8 < -5 + 17x
13 < 17x
13/17 < x
3x-8(1-x)≥5x-4
3x - 8 + 8x ≥ 5x - 4
6x - 8 ≥ - 4
6x ≥ 4
x ≥ 2/3